La desintegración familiar y rendimiento académico en los estudiantes de octavo, noveno y décimo año de educación general básica del Instituto Técnico Saraguro de la ciudad de Saraguro durante el año 2014 - Ureña Salcedo, Roberth Stalin (2015)
This thesis: Family disintegration and academic performance among students in eighth, ninth and tenth year of Basic General Education Saraguro Technical Institute in the city of Saraguro in 2014, has the general objective to identify the incidence of family breakdown in the academic performance of students in eighth, ninth and tenth years of Saraguro Technical Institute in the city of Saraguro, period 2014. The type of study is descriptive; the sample was composed of 216 students; the methods used were scientific, deductive-inductive, analytic-synthetic, descriptive; the techniques and instruments used were the survey to students; the results found that family breakdown is manifested through alcoholism by a parent; the cumulative academic performance reaches the required learning; and verified that family breakdown causes poor academic performance. We conclude that the causes of family disintegration is to prevail alcohol addictions by one parent, the range of the evaluation, characterizes the academic performance of students meeting the learning required; and family breakdown affects the academic performance of students